Predictors and outcomes of acute kidney injury after non-cardiac paeditaric surgery. (2019)
Background: It is necessary to define the problem of acute kidney injury (AKI) after non-cardiac surgery in order to design interventions to prevent AKI. The study aimed to evaluate the occurrence, determinants and outcome of AKI among children undergoing general (non-cardiac) surgery. Methods: This was a prospective cohort study of patients aged ≤ 15 years who had general surgery over 18 months period at a tertiary hospital in Nigeria. AKI was evaluated at 6 and 24 h and within 7 days of surgery. Data were analysed using SPSS version 21. Results: A total of 93 patients were studied with age ranging from 3 days to 15 years (median = 4 years). AKI occurred within 24 h of surgery in 32 (34.4%) and cumulatively over 7 days in 33 (35.5%). Patients who had sepsis were nearly four times as likely as others to develop perioperative AKI (OR = 3.52, 95% CI 1.21, 10.20, p = 0.021). Crude mortality rate was 12.1% (4/33); no mortality was recorded among those without AKI, p = 0.014. Conclusion: Perioperative AKI occurred in 35.5% of children who underwent general (non-cardiac) surgery. Patients who had sepsis were four times more likely than others to develop AKI. Mortality was documented only in patients who had AKI.